Climate policy innovation: a sociotechnical transitions perspective - Upham, Paul; Kivimaa, Paula; Mickwitz, Per; Åstrand, Kerstin (Environmental politics, 2014)
Seeking to develop a novel understanding of how climate policy innovation (CPI) emerges and spreads, we conceptualise three types of CPIs - genuinely original, diffusion based, and reframing based - and relate these to the sociotechnical transitions literature, particularly the multi-level perspective (MLP) that explains change through interaction between 'niche', 'regime', and 'landscape' levels. Selected climate-related transport policies in Finland, Sweden, and the UK are used to illustrate five hypotheses that connect these concepts from the MLP to particular types of CPI. 'Original' policy innovation may be uncommon in contexts with major sunk investments such as transport, principally because sociotechnical regimes tend to be resistant to political pressures for change originating at the same level. Nonetheless, the MLP posits that regimes are subject to influence by pressures originating at both niche and landscape levels. Given that policy reframing is relatively common, it may offer a key entry point for CPI in the short to medium term.